Baptisan Menggerejakan Umat: Menyikapi Penginjilan menurut Matius 28:19-20 - Rasid Rachman (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. Some groups within Christianity, based on Matthew 28:19-20, associate the command to baptize with Christianization. This exposition shows that Jesus' mandate to His own disciples is to disciple all nations rather than to Christianize them. Discipling all nations mean educating and instructing everyone as the church's mission. Through literature study of mission, the history of baptismal liturgy, ritual practice, and my interpretation on Matthew 28:19-20, showing that Jesus commanded the disciples to disciple all nations and to cultivate the people. The results of the study show two things. First, Jesus' mandate in Matthew 28:19-20 is directed to baptized people to carry out the church's mission. Second, the church's mission as a manifestation of Jesus' mandate is a movement to educate and instruct the world, rather than Christianization. The implication of educating and instructing is to cultivate the people of the Church as a community of learners.Abstrak. Beberapa pihak dalam kekristenan, berdasarkan Matius 28:19-20, mengaitkan perintah membaptis dengan kristenisasi. Paparan ini menunjukkan bahwa amanat Yesus kepada para murid adalah untuk memuridkan semua bangsa lebih dahulu ketimbang mengkristenkan. Memuridkan semua bangsa adalah mencerdaskan dan membelajarkan semua orang sebagai misi penginjilan gereja. Melalui kajian pustaka terhadap sejarah liturgi baptisan, praktik ritual, misi, dan tafsiran saya terhadap Matius 28:19-20 memperlihatkan Yesus memerintahkan para murid memuridkan semua bangsa dan menggerejakan umat. Hasil kajian memperlihatkan dua hal. Pertama, amanat Yesus dalam Matius 28:19-20 ditujukan kepada umat baptisan melakukan misi gereja. Kedua, misi gereja sebagai wujud amanat Yesus adalah gerakan mencerdaskan dan membelajarkan dunia, alih-alih kristenisasi. Implikasi mencerdaskan dan membelajarkan adalah menggerejakan umat sebagai umat pembelajar.